Toward an ecotoxicological risk assessment of microplastics: Comparison of available hazard and exposure data in freshwaters - Adam, Véronique; Yang, Tong; Nowack, Bernd (Environmental toxicology and chemistry, 2019)
Microplastics have been detected in freshwaters all over the world in almost all samples, and ecotoxicological studies have shown adverse effects of microplastics on organisms. However, no risk assessment of microplastics has been performed specifically in freshwater so far. The aim of the present study was therefore to review all exposure and ecotoxicity data available for microplastics in freshwaters and to perform a preliminary probabilistic risk assessment. The exposure probability distribution was based on 391 concentrations measured in Asia, Europe, and North America. Because exposure data are mainly available in particle number–based metrics but results from hazard studies are mostly mass‐based, the hazard results were converted into particle number concentrations. A statistical analysis of the hazard data showed that there was no significant influence of particle shape or type of polymer on the no‐observed‐effect concentration. The predicted‐no‐effect concentration (PNEC) was calculated as the fifth percentile of the probabilistic species sensitivity distribution, based on 53 values from 14 freshwater species, to have a mode of 7.4 × 105 particles · m−3 (25th and 75th quantiles of 6.1 × 105 and 1.3 × 106 particles · m−3, respectively). The exposure probability distribution was divided by the PNEC probability distribution to calculate risk characterization ratios (RCRs), with modes of 1.3 × 10−6 in North America, 3.3 × 10−6 in Europe, and 4.6 × 10−3 in Asia. Probability distributions associated with the RCRs showed that ecological risks cannot be entirely excluded in Asia, where 0.4% of the RCR values were above 1. Environ Toxicol Chem 2019;38:436–447. © 2018 SETAC The environmental risk of microplastics was assessed using a probabilistic approach in the freshwaters of Asia, Europe, and North America. Results show that such risks cannot be excluded in Asia.